TANTANGAN IMPLEMENTASI KURIKULUM MERDEKA DI SDN PASAR LAMA 6: ANALISIS ASESMEN DAN PEMBELAJARAN BERDIFERENSIASI - Septiana Devi Puspitasari; Aina Dheabadra; Hayatun Syifa; Fatimatuz Zhahra; Diani Ayu Pratiwi; Aslamiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the Independent Curriculum at SDN Pasar Lama 6, focusing on the implementation of diagnostic assessments and differentiated learning. Diagnostic assessments are used as an initial step in identifying students' learning styles and mapping their interests, but the results are not always accurate because they are influenced by individual conditions when the assessment is carried out. Therefore, teachers conduct periodic evaluations to adjust learning strategies to be more effective. In implementing differentiated learning, schools implement heterogeneous student grouping to encourage collaboration and improve understanding of the material. The learning methods used vary, including inquiry models and project-based approaches, which allow students to be more active in the learning process. In addition, various supporting programs such as morning literacy, Healthy Friday, and milk drinking programs are implemented to improve students' well-being and learning motivation. Support from schools and teacher communities also plays an important role in the success of the implementation of the Independent Curriculum, where teachers actively participate in learning communities and training to improve their competencies. With the strategies implemented, it is hoped that the Independent Curriculum can run more optimally and provide a more meaningful learning experience for students.